A review of hydropower plants in Romania: Distribution, current knowledge, and their effects on fish in headwater streams. (July 2021) - Costea, Gabriela; Pusch, Martin T.; Bănăduc, Doru; Cosmoiu, Diana; Curtean-Bănăduc, Angela
Abstract: Hydropower is currently experiencing a boom in southeast Europe. For Romania, the number of hydropower plants is estimated to be between 545 and 674, but little has been published about their environmental impact. We provide the first overview of the geographical distribution of hydropower plants in Romania, supplemented by a review of current knowledge about their environmental impact, and present case study evidence on the effects of small hydropower plants on fish in headwater streams of the Carpathian Mountains. We show that 49% of the documented 545 hydropower plants in Romania are located in Natura 2000 or other protected areas, 5% are located in water bodies with 'very good' ecological status, and another 12% in water bodies with 'good' ecological status and 'very good' hydromorphological status according to the EU Water Framework Directive. Second, we demonstrate that hydropower plants significantly impact fish populations in several ways, both in upstream and downstream reaches, e.g. by water abstraction, dam construction and other hydromorphological alterations. Following the construction of hydropower plants in headwater streams, trout ( Salmo trutta fario ) and bullhead ( Cottus gobio ) populations often disappeared completely, and only remained in 38% of the stream reaches either upstream or downstream of the respective hydropower plants. In conclusion, the significant environmental impacts of each individual hydropower plant combined with the large number of them as well as the relative lack of effort to mitigate environmental impacts together represent a significant threat to aquatic biodiversity in Romania. The impacts exerted by hydropower plants are often unjustifiable by public interest according to EU directives, as small hydropower plants account for only around 3% of Romania's total electricity production. Better availability and access to environmental monitoring data are needed, as this would greatly support the development of more integrative management approaches to Romanian rivers. Graphical abstract: Image 1 Highlights: The first map of the 545 known hydropower plants in Romania. 49% of Romanian HPPs are located in Natura 2000 and other nature protection areas. Data from 32 hydropower plants sheds light on the impacts of hydropower plants on fish communities. The many small HPPs severely threaten aquatic biodiversity in Romania, while they produce only c. 3% of total electricity.